Presence of plastic litter in pellets from Great Cormorant (Phalacrocorax carbo) in Ireland. Issue 1 (15th April 2017) - Acampora, Heidi; Berrow, Simon; Newton, Stephen; O'Connor, Ian
Abstract: Plastic pollution has been the subject of much research in the last decade. Seabirds can mistake plastic fragments for prey, which can perforate or block the digestive tract and cause ulcers. Most commonly, seabirds accumulate this indigestible matter in their stomachs, obtaining no nutrition and may die from starvation. Certain species of seabirds however, have the ability of regurgitating indigestible matter in the form of pellets. This study aimed to investigate the ingestion of plastics by live seabirds through the examination of regurgitated pellets (n = 92) from a Great Cormorant ( Phalacrocorax carbo ) breeding colony and a winter roost in Ireland. Plastic prevalence was consistently 3.2% at both sites. The presence of plastic litter highlights the fact that all species of seabird are susceptible to interact with marine litter regardless of feeding habits, although at different rates. More research is needed to understand the driving factors involved in plastic ingestion among different species. Highlights: First assessment of ingestion of plastics by Great Cormorants in Ireland First assessment of ingestion of plastics by live adult birds through pellets in Ireland 3.2% of pellet samples (n = 92) contained plastic litter